Pengembangan Kecerdasan Emosi Untuk Meningkatkan Sikap Sosial Siswa Sekolah Dasar - Sastradiharja, EE. Junaedi; Sarnoto, Ahmad Zain; Nurikasari, Neneng (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
This study aims to know the improvement of emotional intelligence of students' social attitudes at elementary school of Al Azhar Syifa Budi Telaga Bestari Tangerang. This research used case study of qualitative research methods and the instruments were interviews, observations and document studies. Data analysis used reduction, display and verification. The sample were five teachers as main informants and five students as supporting informants. The results of this study were (1) the the improvoving step of emotional intelligence on the students’ social attitudes through giving advice, good examples, character building, and a high sense of solidarity to build a sense of sympathy and empathy for others. (2) Efforts of improving students’ emotional intelligence was by increasing students’ self-motivation, fostering relationships and cooperation, training students' empathy, controlling and expressing emotions. (3) Factors that effects students’ emotional intelligence on improving the students’ social attitudes were from the family environment, the family whose had not enough religion relatively difficult to control. Then, the community environment, can affect the student’s attitude with a good or bad relationship between students and teachers. They became more responssible for their behavior. They were also more careful in their actions.